Arbutin attenuates LPS-induced lung injury via Sirt1/ Nrf2/ NF-κBp65 pathway. (February 2019) - Ye, Jinyan; Guan, Minqiang; Lu, Yao; Zhang, Dan; Li, Chengye; Zhou, Caicun
Abstract: The main goal of this study was to evaluate the effects of arbutin (AR) on lipopolysaccharide (LPS)-induced lung injury. A lung injury rat model was established by intravenous LPS administration. We found that levels of inflammatory cytokines, including tumor necrosis factor-alpha (TNF-α), interleukin-1 beta (IL-1β), and interleukin-6 (IL-6) in both serum and lung tissue were significant increased after LPS challenge. In addition, pathological conditions were examined in rat lungs, and it was demonstrated that AR-pretreatment reduced LPS-induced malondialdehyde (MDA) levels and increased LPS-induced superoxide dismutase (SOD) activity. Moreover, the expression of sirtuin1 (SIRT1), nuclear erythroid factor 2-related factor 2 (Nrf-2), heme oxygenase-1 (HO-1) as well as the phosphorylation of NF-κBp65 and IκBα were increased with LPS-induced lung injury, and were significantly restored by AR treatment. Together, our results indicated that SIRT1 is a potential therapeutic target in LPS-induced lung injury, and that AR may be a novel therapeutic in patients with acute lung injury.